Pengaruh Beauty Influencer terhadap Minat Beli Produk Kosmetik di Kalangan Followers Akun Tiktok @tasyafarasya - Gendis Fahira Atsiilah; Tanti Hermawati (Jurnal Komunikasi Massa, 2025)
The development of technology and social media has provided new opportunities in marketing strategies, including through the use of beauty influencers on TikTok. This study aims to examine the effect of argument quality, source credibility, and source attractiveness of the @tasyafarasya TikTok account on purchase intention of cosmetic products among followers. This research framework is based on the Elaboration Likelihood Model (ELM) theory with a focus on the persuasion process through central and peripheral routes. This research uses a descriptive quantitative method with a questionnaire survey as a data collection instrument. The research sample involved 100 respondents who were followers of the @tasyafarasya TikTok account. The data obtained were analyzed using multiple linear regression statistical tests to measure the effect of each independent variable on purchase intention. The results showed that argument quality, source credibility, and source attractiveness have a significant positive effect on purchase intention of cosmetic products. Simultaneously, the three variables also have a significant influence on purchase intention. This finding confirms that marketing strategies through beauty influencers with convincing narratives, high credibility, and strong appeal can encourage an increase in consumer purchase intention.